A Scientometric Study on Biodiesel Development in Indonesia - Mesnan Silalahi; Agus Santoso; Dudi Hidayat (STI Policy and Management Journal, 2019)
This paper describes the results of scientometric studies in the energy sector, especially in the field of biofuel and or biodiesel in Indonesia using a mixed method. Quantitative research using bibliometric basics and content analysis with text mining is triangulated with the results from in-depth interview with several prominent researchers in this field. Content analysis is done with topic modeling method using abstract of papers indexed in Scopus. This article reports on the results of research scientometric study in the energy sector especially in the field of biofuel and or biodiesel in Indonesia, which is expected to provide input and recommendations in the national priority program energy research policies and strategies. The impact is the making of national research policies based on evidence.